A systematic correlation of morphology and function using spectral domain optical coherence tomography and microperimetry in patients with geographic atrophy. Issue 8 (7th April 2014) - Sayegh, Ramzi G; Kiss, Christopher G; Simader, Christian; Kroisamer, Julia; Montuoro, Alessio; Mittermüller, Tamara J; Azhary, Malek; Bolz, Matthias; Kreil, David P; Schmidt-Erfurth, Ursula
Abstract : Aims: This study has been designed to describe the functional impact of distinct pathologies within the retinal layers in patients with geographic atrophy (GA) by means of a point-to-point correlation between optical coherence tomography (OCT) and microperimetry. Methods: Retinal morphology and function of 23 patients suffering from GA of the retinal pigment epithelium (RPE) have been investigated using the Spectralis OCT (Heidelberg Engineering) and the MP1 microperimeter (Nidek Technologies). The point-to-point overlay of morphology and function has been done using proprietary software, allowing OCT image grading to define distinct alterations of the neurosensory retina, the RPE and the choroid. By overlaying the retinal sensitivity map on the OCT data set, retinal layer alterations could be evaluated regarding their impact on visual function. Results: A total of 1005 stimulation points in the lesion area in 2107 spectral domain OCT B-scans were graded in 43 eyes of 23 patients (mean best corrected visual acuity=20/70). Retinal sensitivity decreases with an increasing number of morphological alterations graded (p<10 −13 ). Alterations of the RPE and the external limiting membrane (p<0.02) were associated with absolute scotomas. Furthermore, the loss of the external limiting membrane as the largest area of morphological alteration among our patients with GA (mean area=5.65 mm 2 ), had a significant impact (p<10 −4 ) on sensitivity (−1.3 dB). Conclusions: Mapping retinal sensitivity to distinct retinal pathologies revealed outer retinal layers, in addition to the RPE, as significant for sensitivity loss. Therefore in GA the RPE loss and the alteration of outer retinal layers should be analysed, which could also provide insight into lesion progression.